Desgaste - a presença transformadora do artista - Costa, Mirieli (2013)
The dissertation proposal is to reflect on the presence of the artist through the work during the master's research, trying to understand the artist in the process of this artwork. The theoretical and practical framework of the dissertation seeks to understand the artist's presence and be doing stuff as founder of the work. To think of the changes that lead artist and their work process to become. In the artist's own voice, your presence and your tackle to the public are taken as fundamental elements of this research, seeking support in the thought of Bergson and Deuleze to understand the transformations of poetic and contextualize these elements in Contemporary Art.